Identidades (trans)viadas: existências banidas e a luta contra as violações naturalizadas, um estudo na cidade de Campina Grande – PB - Rodrigues, Matheus (2021)
The disparities found between cisgender individuals and those who do not fit the imposed social behavior, such as the case of transsexuals, demonstrated in the legal and social spheres, reflect on their experiences of oppression. The way society is organized establishes a structure of violence in which transgender people will have to deal with the lack of respect for their dignity in accessing rights and social inclusion. Considering these assumptions, this study analyzed the repercussions of the right to a social name and the rectification of name and gender for the transsexual, from the perspective of Human Rights, as mitigating mechanisms for discriminatory processes. The objectives that motivated this research were: to Analyze, in a historical perspective, the lives of transsexuals and describe, through a timeline, the way in which transsexuality was perceived in society, according to the project of bourgeois eugenic power, of the antiquity to modernity; Discuss the role of Human Rights and protective means aimed at this minority, at the national level, affected by violence, to make considerations about the performance of Human Rights in the global scenario, based on data on the processes of violence suffered by transsexual people; Present data on violence against trans people in Brazil and the impact of cultural discourses on actions of stereotyping and hate against trans people; To investigate how the applicability and respectability of the use of the social name and the rectification of name and gender occur, through interviews carried out with transsexuals in the Espaço LGBT Luciano Bezerra Vieira, when understanding the terminological distinctions on the normalization of gender, identity and difference, aiming to deconstruct socially established stereotypes. This study is relevant due to the fact that it denounces violence and gives visibility to transsexuals, bringing to light the reality of prejudices experienced daily by these individuals whose living conditions are affected in the most diverse possible perspectives. The research was a qualitative approach, exploratory in nature, using the inductive method, with a literature review based on authors such as Foucault (2018, 2019), Butler (2019), Miskolci (2012), Hall (2009, 2016), Bento (2006), among others, and used the Constitution, the Civil Code and data from Associação Nacional de Travestis e Transexuais - ANTRA (the National Association of Transvestites and Transsexuals - ANTRA). A field research was carried out, with semi-structured interviews, at Centro Estadual dos Direitos de LGBT e Enfrentamento à LGBTfobia (the State Center for LGBT Rights and Fighting LGBTphobia), located in the city of Campina Grande - Paraíba. The interviewed subjects were transsexuals assisted by the Espaço, who aim to carry out the procedures for rectification and/or documentation of the social name. The general results show that the reality of daily violations related to transsexual people is circumvented by structural aspects of a segregating society, which impedes access to dignifying basic rights, as well as perpetrates the absence of a quality transsexualizing process and reveals low social insertion in collective spaces that continue perpetuating discourses of dehumanization to those who break with normativity.